Psalmsic Prophecies as Evidence that Jesus is the Messiah - Yusak Tanasyah; Wahyudi Purnomo; Handreas Sudarmiko Akimas; Steven Phang (Journal of Religious and Socio-Cultural, 2024)
This journal article explores the prophecies found in the Book of Psalms, employing a hermeneutical research method to argue that these prophecies serve as substantial evidence for the claim that Jesus is the Messiah. Through a detailed examination of key Psalms traditionally considered messianic, the article highlights the historical, literary, and theological dimensions of these texts, demonstrating their fulfillment in the life, death, and resurrection of Jesus Christ. The Book of Psalms, a central text in the Hebrew Bible, contains numerous passages that have been interpreted as prophetic references to the coming Messiah. This article aims to provide a comprehensive analysis of these Psalms, employing hermeneutics to uncover their messianic significance and to present a compelling case for Jesus of Nazareth as the fulfillment of these ancient prophecies. Using the hermeneutical research method, this study examines the Psalms through multiple lenses: historical context, literary analysis, theological exegesis, canonical context, and reception history. This multifaceted approach ensures a thorough understanding of the text and its implications. Through hermeneutical analysis, this article provides substantial evidence that the messianic prophecies in the Psalms find their fulfillment in Jesus Christ. The convergence of historical, literary, and theological insights underscores the coherence and credibility of the claim that Jesus is the promised Messiah. This study not only enriches our understanding of the Psalms but also strengthens the theological foundation for Christian belief in Jesus as the Messiah.